Effects of Health on Wages of Australian Men - Cai, L (My University, 2009)
This study uses the Household, Income and Labour Dynamics in Australia (HILDA) survey to investigate the effect of health on wages of working-age Australian men. A simultaneous equation model of health and wages is estimated to account for the endogeneity of health. The results confirm the findings in the literature that health has a significant and positive effect on wages; it is also found that treating health as exogenous underestimates the effect substantially. Although the reverse effect of wages on health is found to be insignificant, there is evidence on the endogeneity of health arising from unobserved factors.
Economic Record
Keywords: Gender -- Male; Gender; Health; Gender; Health and wellbeing; Health; Gender; Male; Health and wellbeing; Gender